Perceived injustice in patients with chronic pain - Tilman Wolter; Barbara Kleinmann (BioPsychoSocial Medicine)
Abstract Background Chronic pain, particularly pain secondary to trauma, is often accompanied by a feeling of perceived injustice. A prevalent feeling of injustice often goes along with a prolonged rehabilitation and problematic development of chronic pain. This feeling also correlates to catastrophizing. To date, too little is known about how the perception of injustice in chronic pain patients is interwoven with a variety of psychological, social and somatic factors. The present study sought to examine whether perceived injustice is correlated with pain level, pain diagnosis, depression, anxiety, stress, quality of life, pain related disability, occupation status and ongoing workers compensation litigation. Material and methods During the three month period, all patients undergoing an interdisciplinary assessment of their chronic pain at our institution (n = 191) were asked to take part in the study. 164 patients (86%) completed the injustice experience questionnaire (IEQ). Data regarding pain level, pain diagnosis, gender, age, depression, anxiety, stress, quality of life, pain related disability, occupation status and ongoing workers compensation litigation were extracted from the patient’s charts. Correlations of these data to IEQ scores and differences between distinct subgroups of patients were analysed. Results Median total IEQ scores were 36.0 (IQR: 29.0–42.75). Median IEQ scores for the subscale blame and severity were 14.0 (IQR: 10.0–19.5) and 21.0 (IQR: 18.0–24.0) respectively. The IEQ correlated statistically significant with anxiety, depression and stress. No statistically significant differences were found in the IEQ scores between men and women. There was no statistically significant correlation of the IEQ scores with age, neither were statistically significant correlations with pain localizations found. No statistically significant correlation between IEQ scores and the different pain scores were found. IEQ values were higher in patients with pension application and with current sick leave. The presence of biographical factors (i.e. childhood trauma or experiences of emotional neglect) was related with higher IEQ values. Conclusion The IEQ appears to be more closely related to psychological and social determinants of pain than to somatic factors.